FACTOR INFLUENCING LENGTH OF STAY (LOS) OF PATIENTS UNDERGOING BYPASS SURGERY AT SHAHEED MADANEE CARDIAC TEACHING HOSPITAL –TABRIZ — IRAN - Reza Gholi Vahidi; Rahim Khodayari; Shabnam lezadi; Kamal Gholipour (Российский кардиологический журнал)
Aim. This study aimed to study the effect of patients’ and physician’s characteristics as a predictor of length of stay (LOS) in patients undergoing coronary bypass surgery.Material and methods. This was a retrospective study conducted at Tabriz Shaheed Madanee Cardiac Teaching Hospital in Iran in 2010. The 349 patients who did undergo a bypass surgery during 2008–2010 were studied. Patients and physicians characteristic were collected from patients medical records using a researcher developed checklist. Independent Samples Test of ANOVA was conducted to compare LOS between categorical variables. Data was analyzed using the SPSS17 statistical package.Results. The mean age of the patients was 59.7 years. Overall average LOS was 15.58 (10.02) days. The findings of this study indicate that older patients stayed in the hospital for a significantly longer period than did younger patients. Patients’ stay at the hospital was statistically significant and longer than assessed expected length of stay estimated by physicians (P< 0.05). Patient admitted to the hospital through emergency department and patients with no hospitalization history stayed longer in the hospital (P≤0.01).).Early discharged patients and death cases also had a longer LOS (P ≤ 0.01).Patient whose attending physicians were working in private sector, in addition to Shaheed Madanee Hospital and had higher level of education stayed longer than those whose physicians worked only at Shaheed Madanee Hospital (P≤ 0.01).Conclusion. Institutional characteristics –physicians practice both in private sector and public teaching hospital, physicians’ level of education, discharge process guidelines, and admission protocols were most important factor in predicting LOS. The patient’s hospitalization history whether patient was hospitalized before or not, was also a predictor.